直动滚子盘形凸轮弹流润滑分析 - 廖海平; 刘启跃; 曾翠华; 李艳玲 (Jixie chuandong)
Wear is one of invalidation form of plate cam with translating roller follower.Lubrication status is the mostly factor of cam worn.based on elasto-hydrodynamic lubrication theory,the calculating methods of the minimal oil film thickness and film thickness ratio of plate cam with translating roller follower are discussed.It is a reference of optimization design to cam based on tribology.